South Korea’s Defense Diplomacy for Long Term Capacity Building through International Military Education in the United States - Nugraha, Deja Akmal; Perwita, Anak Agung Banyu; Inkiriwang, Frega Wenas; Joodael, Kim (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper explores the long-term impact of South Korean military education in the United States on South Korea's defense capacity building. Through qualitative case studies, the research examines the evolution of South Korea's participation in US military education programs and the subsequent utilization of US-trained officers within the South Korean military. The findings reveal significant benefits such as enhanced interoperability, modernization of military tactics, and the development of a highly skilled officer corps. However, the study also addresses challenges including cultural barriers, costs, and political polarization. By providing a comprehensive analysis, this research underscores the critical role of international military education in strengthening South Korea’s defense capabilities and fostering enduring defense partnerships between South Korea and the United States.